2009
DOI: 10.1002/ijc.24454
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of polyphenols, nitrate and nitrite and gastric cancer risk in Mexico City

Abstract: N-Nitroso compounds (NOC) are potent animal carcinogens and potential human carcinogens. The primary source of exposure for most individuals may be endogenous formation, a process that can be inhibited by dietary polyphenols. To estimate the risk of gastric cancer (GC) in relation to the individual and combined consumption of polyphenols and NOC precursors (nitrate and nitrite), a population-based case-control study was carried out in Mexico City from 2004 to 2005 including 257 histologically confirmed GC case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
109
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 43 publications
(77 reference statements)
3
109
1
4
Order By: Relevance
“…51 In other Western countries such as Mexico, US and Canada, lignan intakes were much lower than our results (from 0.35 to 0.86 mg/day). 20,37,52 To our knowledge, there are not descriptive data on dietary lignan intake in Asian populations, but probably their contribution to the total phytoestrogen intake would be low like in our UK health-conscious group (o16%). Several papers have reported on intakes of secoisolariciresinol and matairesinol, 34,60 but most of them did not consider lariciresinol and pinoresinol, which contributed 470% to the total lignans in our cohort.…”
Section: Discussionmentioning
confidence: 70%
“…51 In other Western countries such as Mexico, US and Canada, lignan intakes were much lower than our results (from 0.35 to 0.86 mg/day). 20,37,52 To our knowledge, there are not descriptive data on dietary lignan intake in Asian populations, but probably their contribution to the total phytoestrogen intake would be low like in our UK health-conscious group (o16%). Several papers have reported on intakes of secoisolariciresinol and matairesinol, 34,60 but most of them did not consider lariciresinol and pinoresinol, which contributed 470% to the total lignans in our cohort.…”
Section: Discussionmentioning
confidence: 70%
“…Vegetable intake accounts for ∼80% of dietary nitrate consumption in human diets 10; dietary nitrates can be reduced to nitric oxide (NO) via non‐enzymatic reduction by lingual bacteria and a variety of mammalian reductases and increase NO bioavailability through the nitrate‐nitrite‐NO pathway 11, 12. Gastric metabolism of nitrate and nitrite is associated with both health benefits and risks 13, including the formation of potentially carcinogenic nitrosamines promoted by nitrites in processed meats which can be inhibited by flavonoids and other compounds in vegetables 14. Importantly, both the European Food Standards Agency (EFSA) and a recent NHLBI panel concluded that current research does not support a role for nitrate consumed as vegetables as a carcinogen 10.…”
Section: Introductionmentioning
confidence: 99%
“…More recently begun to be recognized the potential carcinogenic effects of nitrosamines and nitrosamides, generically called N-compounds, substances formed in the interaction between a group of secondary nitrogen (which can be an amine or amide, a urea or an alkyl-ring peptide) and a nitrite. The evidence that the populations most at risk for gastric cancer have diets rich in substrates for the process of endogenous N-compounds triggered the interest in the evaluation of these substances in the genesis of gastric cancer (6) . The N-nitroso compounds, the main source for most people, the endogenous formation, a process that can be inhibited by polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…The N-nitroso compounds, the main source for most people, the endogenous formation, a process that can be inhibited by polyphenols. A case-control study in Mexico City in 2004-2005, including 257 cases with gastric cancer (histologically confirmed) and 478 controls was conducted to estimate the risk of gastric cancer in relation to individual and combined consumption of polyphenols and precursors N-compounds (6) . The intake of polyphenols, nitrate and nitrite were estimated by a food frequency questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation